Preparation and characterization of poly(ε-caprolactone) nanospheres containing the local anesthetic lidocaine - Ramos Campos, Estefânia Vangelie [UNESP]; Silva de Melo, Nathalie Ferreira [UNESP]; Guilherme, Viviane Aparecida; de Paula, Eneida; Rosa, André Henrique [UNESP]; de Araújo, Daniele Ribeiro; Fraceto, Leonardo Fernandes [UNESP] (Elsevier, 2013)
The objective of this work was to develop a modified release system for the local anesthetic lidocaine (LDC), using poly(ε-caprolactone) (PCL) nanospheres (NSs), to improve the pharmacological properties of the drug when administered by the infiltration route. In vitro experiments were used to characterize the system and investigate the release mechanism. The NSs presented a polydispersion index of 0.072, an average diameter of 449.6nm, a zeta potential of -20.1mV, and an association efficiency of 93.3%. The release profiles showed that the release of associated LDC was slower than that of the free drug. Atomic force microscopy analyses showed that the spherical structure of the particles was preserved as a function of time, as well as after the release experiments. Cytotoxicity and pharmacological tests confirmed that association with the NSs reduced the toxicity of LDC, and prolonged its anesthetic action. This new formulation could potentially be used in applications requiring gradual anesthetic release, especially dental procedures. © 2012 Wiley Periodicals, Inc.
Keywords: Analgesia; Anesthetic activity; Controlled release; Drug release; Lidocaine; Nanoparticles; Nanospheres; Nanotechnology; Poly(ε-caprolactone); Polymeric drug carrier; lidocaine; nanosphere; polycaprolactone; animal experiment; animal tissue; atomic force microscopy; controlled study; cytotoxicity; drug formulation; drug release; drug structure; in vitro study; male; mouse; nonhuman; zeta potential; Anesthetics, Local; Animals; BALB 3T3 Cells; Cell Survival; Chemistry, Pharmaceutical; Delayed-Action Preparations; Dose-Response Relationship, Drug; Drug Carriers; Drug Stability; Fibroblasts; Hydrogen-Ion Concentration; Kinetics; Male; Mice; Microscopy, Atomic Force; Motor Activity; Nerve Block; Pain Threshold; Particle Size; Polyesters; Reaction Time; Sciatic Nerve; Solubility; Technology, Pharmaceutical